2018
DOI: 10.1093/ofid/ofy210.1204
|View full text |Cite
|
Sign up to set email alerts
|

1373. Activity of Ceftriaxone–Sulbactam–EDTA Against Multi-Drug-resistant A. baumannii, P. aeruginosa and Enterobacteriaceae Isolates (WHO Critical Priority Pathogens) Collected from Various Hospitals in India

Abstract: BackgroundCeftriaxone–Sulbactam–EDTA (CSE) is the first cephalosporin–β-lactamase inhibitor combination with an antibiotic resistance breaker–disodium edetate, recently evaluated in a Phase 3 clinical trial for treatment of adults with complicated urinary tract infections (NCT03477422). The addition of Sulbactam and EDTA expands the spectrum of activity of Ceftriaxone to include extended-spectrum-β-lactamase (ESBL) and metallo-β-lactamase (MBL) producing bacteria. This study evaluated the in vitro activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…CSE, a novel combination of ceftriaxone, sulbactam, and disodium ethylenediaminetetraacetic acid ([EDTA] a known metal chelator), was developed for the treatment of various bacterial infections. The addition of sulbactam and disodium EDTA expands the in vitro activity of ceftriaxone against Ambler class A ( bla TEM , bla SHV , bla CTX-M ), class B (metallo-enzymes, eg, bla VIM , bla NDM , bla IMP ), and some class D β-lactamase-producing bacteria [12, 13]; it is not active against serine carbapenemases [14]. Furthermore, in in vitro studies, CSE has shown activity against other resistance mechanisms such as efflux pumps [15, 16], bacterial biofilms [17], membrane impermeability [18], and horizontal gene transfer by means of conjugation [19], although the clinical relevance of these is unproven.…”
mentioning
confidence: 99%
“…CSE, a novel combination of ceftriaxone, sulbactam, and disodium ethylenediaminetetraacetic acid ([EDTA] a known metal chelator), was developed for the treatment of various bacterial infections. The addition of sulbactam and disodium EDTA expands the in vitro activity of ceftriaxone against Ambler class A ( bla TEM , bla SHV , bla CTX-M ), class B (metallo-enzymes, eg, bla VIM , bla NDM , bla IMP ), and some class D β-lactamase-producing bacteria [12, 13]; it is not active against serine carbapenemases [14]. Furthermore, in in vitro studies, CSE has shown activity against other resistance mechanisms such as efflux pumps [15, 16], bacterial biofilms [17], membrane impermeability [18], and horizontal gene transfer by means of conjugation [19], although the clinical relevance of these is unproven.…”
mentioning
confidence: 99%